An umbrella review of the use of platelet‐rich plasma in the treatment of androgenetic alopecia. (31st January 2023) - Li, Caihong; Pan, Lingfeng; Yang, Liehao; Kong, Jiao; Zhang, Lianbo
Abstract: Objective: To evaluate the efficacy of platelet‐rich plasma (PRP) in the treatment of androgenetic alopecia, as well as establish an effective treatment protocol and optimal PRP preparation procedure. Methods: We searched the PubMed, Scopus, Embase, Cochrane, CNKI, and Wanfang databases from inception to October 29, 2021, using PROSPERO's International Prospective Register of Systematic Reviews (registration ID: CRD42022295921). Results: The original literature search revealed 215 reviews; after duplication removal, 89 papers were eliminated, 95 were eliminated after reading the titles and abstracts, and eventually, 28 articles were included after reading the complete text. Conclusions: PRP treatment for androgenetic alopecia is effective, and we recommend the following: (1) a PRP volume of at least 0.05 ml/cm 2, preferably 0.1 ml/cm 2 ; (2) at least three consecutive treatments at an interval of 1 month; (3) intensive therapy is beneficial and can be provided from 3 to 6 months after continuous treatment; (4) objective indicators such as hair diameter, hair count; (5) long‐term follow‐up.